Decreased dopaminergic treatment of hospitalized Parkinson's disease patients during infectious diseases is associated with poor outcomes. Issue 8 (August 2015) - Segal, O.; Hassin-Baer, S.; Rosman, M.; Segal, G.
Abstract: A retrospective analysis of consecutive Parkinson's disease (PD) patients hospitalized in internal medicine wards during the years 2008 to 2013 due to infectious disease was performed. PD patients are prone to infections, often leading to hospitalization in internal medicine wards. We observed that during these hospitalizations, chronic anti-Parkinson's medications are frequently overlooked and withdrawn, their reintroduction is delayed and dosages are decreased. Only patients on chronic therapy with at least one anti-Parkinson's medication were included in this study. Multivariate analyses established the association between medication dose reductions on short-term clinical outcomes, including in-hospital mortality and change in discharge destination. Medical records from 528 PD patients were analyzed and 430 were excluded. Of the 98 included, 53 had pneumonia and 58 had urinary tract infections. The overall in-hospital mortality rate was 11.2%. 56.1% of patients' dopaminergic medications were decreased in dose upon admission (22.5% mean decrease in levodopa equivalent daily dose [LEDD]; p  < 0.001). Both absolute and relative LEDD reductions were associated with significantly increased in-hospital mortality (mean reduction of 394.5 mg versus 188.4 mg; p  = 0.035 by analysis of variance adjusted to age, sex and renal function) and was also associated with worse discharge destination relative to original place of arrival (mean reduction of 377.8 mg versus 150.7 mg; p  = 0.014). Decreased dopaminergic medication dosing upon admission of PD patients due to infection is widespread and potentially associated with worse clinical outcomes.